Parasitism performance of Aenasius bambawalei (Hayat) on Phenacoccus solenopsis (Tinsley): Parasitism performance of A. bambawalei - Soomro, Din Muhammad; Solangi, Bhai Khan; Alhilfi, Ali Zachi Abdulqader; Kapri, Abdul Qadir; Ishfaque, Muhammad; Rajput, Imran Ali; Chand, Kirshan; Lashari, Muhammad Akbar; Abbasi, Faiza; Rashdi, Syed Muzafar Ali Shah; et al. (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2022)
Aenasius bambawalei Hayat (Hymenoptera: Encyrtidae) is a solitary nymphal endoparasitoid of mealybug, Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae). The parasitism performance of A. bambawalei on the 3rd nymphal instar of P. solenopsis at different densities 20, 30, 40 and 50 P. solenopsis was tested. The results showed that the maximum number of P. solenopsis parasitized and male and female adults emerged at 30 P. solenopsis density than other densities. Similarly, the maximum sex ratio M: F (1: 1.7) was found at 50 P. solenopsis density as compared to others. The highest parasitization percentage was observed on 3-day old A. bambawalei at all P. solenopsis densities. The 30 P. solenopsis density is the most preferred and suitable for mass rearing of A. bambawalei and the 3-day old parasitoid use of biological control programme to control P. solenopsis.